Sob o signo do Caduceu. Hospital de Caridade São João de Deus : representação social e cultural (Laranjeiras/SE, 1996 - 2012) - Cavalcante, Danielle de Oliveira (2014)
Laranjeiras is the second oldest city in the state of Sergipe, registered by the Institute of National Historical and Artistic Heritage (IPHAN) since 1996, is presented as in Brazil where few still stands strong presence of material culture configured in vernacular architecture. Over the years, this historic city has suffered from various social and urban transformations. In the year 1864, pass the second epidemic of cholera. No hospital and no aid to improvements in population health, was implemented in 1866 the Charity Hospital São João de Deus as an alternative to alleviate the suffering of families laranjeirenses, an institution linked to the Santa Casa de Misericordia, work until the second half of the twentieth century bringing a great contribution to the treatment of local health. Therefore, this study aims to identify, through historiography, which would have been the old Charity Hospital São João de Deus, allowing a perspective of analysis of social representations present in this urban site today in ruin. Comparing to search through bibliographic sources such as reports President of the Province, Periodicals, Books memoirists, and oral sources (interviews) and material sources (Ruins). Data were analyzed qualitatively, allowing more objective view information collected through both the literature researched as what was collected among respondents, for a better analysis of the researched object and represented. Well being of fundamental importance, finish the job with the material culture, the importance of this study and interpreting the ruins of this heritage, emphasizing the aspects and completing the official documentation does not tell us about such spaces. Understood as an urban heritage still analyzes the representation of society Laranjeirense through local social interpretation.